Characterization of fast and slow diffusion from diffusion‐weighted MRI of pediatric Crohn's disease. Issue 1 (24th August 2012) - Freiman, Moti; Perez‐Rossello, Jeannette M.; Callahan, Michael J.; Bittman, Mark; Mulkern, Robert V.; Bousvaros, Athos; Warfield, Simon K.
Abstract Purpose: To characterize fast and slow diffusion components in diffusion‐weighted magnetic resonance imaging (DW‐MRI) of pediatric Crohn's disease (CD). Overall diffusivity reduction as measured by the apparent diffusion coefficient (ADC) in patients with CD has been previously demonstrated. However, the ADC reduction may be due to changes in either fast or slow diffusion components. In this study we distinguished between the fast and slow diffusion components in the DW‐MRI signal decay of pediatric CD. Materials and Methods: We acquired MRI from 24 patients, including MR enterography (MRE) and DW‐MRI with 8 b‐values (0–800 s/mm2). We characterized fast and slow diffusivity by intravoxel incoherent motion (IVIM) model parameters (f, D*, D), and overall diffusivity by ADC values. We determined which model best described the DW‐MRI signal decay. We assessed the influence of the IVIM model parameters on the ADC. We evaluated differences in model parameter values between the enhancing and nonenhancing groups. Results: The IVIM model described the observed data significantly better than the ADC model (P = 0.0088). The ADC was correlated with f (r = 0.67, P = 0.0003), but not with D (r = 0.39, P = 0.062) and D* (r = −0.39, P = 0.057). f values were significantly lower (P < 0.003) and D* values were significantly higher (P = 0.03) in the enhancing segments, while D values were not significantly different between the groups (P = 0.14). Conclusion: For this study population the IVIM model provides a better description of the DW‐MRI signal decay than the ADC model. The reduced ADC is related to changes in the fast diffusion rather than to changes in the slow diffusion. J. Magn. Reson. Imaging 2013;37:156–163. © 2012 Wiley Periodicals, Inc.